Promosi Penjualan Kilat dan Iklan Pesan Singkat Free Bea Kirim dalam mempengaruhi Keputusan Membeli Spontan bagi Mahasiswa Pengguna Aplikasi Shopee di Sekolah Tinggi Ilmu Administrasi Malang - Marhaeni, Tri; Dewantara, C Evie; Chandra, Eddy; Rochma Suprayitno, Intan Nur (STIA MALANG, 2024)
The aim of this research is to analyze the impact of flash sales promotions and free shipping short messages on the Shopee online market (marketplace) on spontaneous (impulse) buying decisions. The research population was 1354 with the criteria being active students at STIA Malang and the sample taken was 135 (10%) people using the purposive sampling method, followed by simple random sampling. The data was analyzed using multiple linear regression. The results of the research showed that flash sale promotions were proven. real and positive impact on spontaneous (impulsive) purchasing decisions. Besides that, the short message advertising variable (tagline) has an influence on spontaneous buying decisions and the contribution of this variable is greater than the flash sales promotion variable. Together, flash sale promotions and free shipping short message advertisements (taglines) have a real and positive effect on spontaneous (impulsive) purchasing decisions. The coefficient of determination test shows a fairly close relationship between flash sales promotions and short message advertisements (taglines) with spontaneous buying decisions and a contribution of 67.5% to the spontaneous buying decision variable (impulsive), while 32.5% influenced by other variables not explained in this study. The research results are in accordance with the theory used and the results of other researchers. The recommendation given is that the Shopee marketplace should immediately innovate in carrying out sales promotions and advertising, because there are many attractive sales promotions from other marketplaces to attract customers